The Effectiveness of the Ukrainian Protestant Media: Results of a Sociological Survey - Balaklitsky, Maxim (Bogoslovskie razmyšlenija, 2011)
Secular and religious researchers, studying this subject, run together in the desire to determine how interesting the informational product to the secular audience is. The researches lack the look from inside such as studying the evaluation of the religious mass media by their main audience - members of religious organizations. To fill in this lacuna we carried out a psychological survey not only of the TV and radio, but also press and Internet Ukrainian Protestant mass media audience and staff. The carried out survey of the Protestant mass media staff and audience revealed that the religious mass media belong to the specialized types of publications. Their influence upon the target audience group, members of the religious community is deep and stable, at the same time the missionary potential is quite low. The complex of factors, which accompanies conversion, correspond with interpersonal and group, but not the mass communication.The confessional mass media are the area of the religious subculture existence. The confidence of Protestants to their publications is very high, though it combines with the critical and evaluating approach. The social subject is the most demanded by the Ukrainian Protestant media. The organized aid for the socially deprived is the main manifestation of the public position of Protestants in our